Kształtowanie relacji z pracownikami jako płaszczyzna społecznej odpowiedzialności biznesu: Development of relations with employees as plane of social responsibility - Bombiak, Edyta (Management and Administration Journal, 2021)
One of the most important areas of corporate social responsibility are now relationswith employees. Caring for them is an effective way to build intellectual capital constitutesa unique source of competitive advantage of modern organizations. Unfortunately, in this dayand age, when we measure the success of the company is to gain many employers forget aboutneglecting their employees. In organizations where managers recognize and understand the role of human capital CSR is a natural part of human resource management strategy.